2023
DOI: 10.1007/s11804-023-00344-8
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Yield-Surface Plasticity State-Based Peridynamics Model and its Applications to Simulations of Ice-Structure Interactions

Ying Song,
Luwen Zhang,
Shaofan Li
et al.

Abstract: Due to complex mesoscopic and the distinct macroscopic evolution characteristics of ice, especially for its brittle-to-ductile transition in dynamic response, it is still a challenging task to build an accurate ice constitutive model to predict ice loads during ship-ice collision. To address this, we incorporate the conventional multi-yield-surface plasticity model with the state-based peridynamics to simulate the stress and crack formation of ice under impact. Additionally, we take into account of the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…To solve the matrix problem (35), the number of modes ψ n (y) is limited to a finite number N mod . Then, the vector ⃗ a is decomposed into its real and imaginary parts, ⃗ a = ⃗ a R + i⃗ a I .…”
Section: Methods Of the Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…To solve the matrix problem (35), the number of modes ψ n (y) is limited to a finite number N mod . Then, the vector ⃗ a is decomposed into its real and imaginary parts, ⃗ a = ⃗ a R + i⃗ a I .…”
Section: Methods Of the Solutionmentioning
confidence: 99%
“…Results of studies on ice destruction can be found in, for example, [33,34]. The conventional multi-yield-surface plasticity model with the state-based peridynamics was studied to simulate the stress and crack formation of ice under impact in [35].…”
Section: Introductionmentioning
confidence: 99%